Effect of housework on physical activity during transitions to parenthood. Issue 1 (2nd January 2021) - Divine, Alison; Blanchard, Chris; Naylor, Patti-Jean; Benoit, Cecilia; Symons Downs, Danielle; Rhodes, Ryan E.
ABSTRACT: The transition to parenthood is associated with declines in moderate to vigorous physical activity (MVPA) and increases in light PA (LPA). One potential mechanism for this change in PA that occur at the onset of parenthood is housework. We examined housework load and PA levels of three cohorts of couples across 12 months recruited from Victoria, British Columbia, Canada between January 2007 and December 2011. Participants (N = 314; 102 not expecting a child, 136 expecting first-child, 76 expecting second child) completed baseline demographics and 7-day accelerometry, followed by assessments at 6 and 12 months. Hierarchical linear regression assessed the association between PA, housework, and perceptions of partner's workload. New fathers' but not new mothers' housework was positively related to their LPA at 12 months. Perceptions of partners' workload were positively related to new mothers LPA, and negatively related to new fathers MVPA at 12 months. Mediation analysis determined if perceived behavioral control accounts for the relationship between the discrepancy in housework between partners' PA. Results suggest that if a woman perceives their partner to do more housework their own PA increases, whereas for men their PA decreases. These findings highlight the importance of the division of housework on PA for both mothers and fathers.